Knowledge, attitudes, anxiety, and preventive behaviours towards COVID-19 among health care providers in Yemen: an online cross-sectional survey - Gamil Ghaleb Alrubaiee; Talal Ali Hussein Al-Qalah; Mohammed Sadeg A. Al-Aawar (BMC, 2020)
Abstract Background The growing incidence of coronavirus (COVID-19) continues to cause fear, anxiety, and panic amongst the community, especially for healthcare providers (HCPs), as the most vulnerable group at risk of contracting this new SARS-CoV-2 infection. To protect and enhance the ability of HCPs to perform their role in responding to COVID-19, healthcare authorities must help to alleviate the level of stress and anxiety amongst HCPs and the community. This will improve the knowledge, attitude and practice towards COVID-19, especially for HCPs. In addition, authorities need to comply in treating this virus by implementing control measures and other precautions. This study explores the knowledge, attitude, anxiety, and preventive behaviours among Yemeni HCPs towards COVID-19. Methods A descriptive, web-based-cross-sectional study was conducted among 1231 Yemeni HCPs. The COVID-19 related questionnaire was designed using Google forms where the responses were coded and analysed using the Statistical Package for the Social Sciences software package (IBM SPSS), version 22.0. Descriptive statistics and Pearson's correlation coefficient test were also employed in this study. A p-value of < 0.05 with a 95% confidence interval was considered as statistically significant. The data collection phase commenced on 22nd April 2020, at 6 pm and finished on 26th April 2020 at 11 am. Results The results indicated that from the 1231 HCPs participating in this study, 61.6% were male, and 67% were aged between 20 and 30 years with a mean age of 29.29 ± 6.75. Most (86%) held a bachelor's degree or above having at least 10 years of work experience or less (88.1%). However, while 57.1% of the respondents obtained their information via social networks and news media, a further 60.0% had never attended lectures/discussions about COVID-19. The results further revealed that the majority of respondents had adequate knowledge, optimistic attitude, moderate level of anxiety, and high-performance in preventive behaviours, 69.8, 85.10%, 51.0 and 87.70%, respectively, towards COVID-19. Conclusion Although the Yemeni HCPs exhibited an adequate level of knowledge, optimistic attitude, moderate level of anxiety, and high-performance in preventive behaviours toward COVID-19, the results highlighted gaps, particularly in their knowledge and attitude towards COVID-19.